Discovery of gramicidin A analogues with altered activities by multidimensional screening of a one-bead-one-compound library - Yuri Takada (Nature Portfolio, 2020)
The strong hemolytic activity and mammalian cytotoxicity of gramicidin A, a peptide antibiotic, has hindered its non-topical clinical application. Here, the authors report a high-throughput strategy for the discovery of gramicidin A analogues with altered biological activity profiles.